Achieving Superplastic Elongations in an AZ80 Magnesium Alloy Processed by High‐Pressure Torsion. Issue 9 (3rd July 2022) - Alsubaie, Saad A.; Bazarnik, Piotr; Huang, Yi; Lewandowska, Malgorzata; Langdon, Terence G.
Abstract : High‐pressure torsion (HPT) is a technique used successfully to refine the grains of an alloy to the submicrometer and nanometer scale. Grain refinement can improve the mechanical properties of magnesium alloys as well as enhancing its ductility and providing a potential for exhibiting superplastic behavior at elevated temperature. Research is conducted to process the AZ80 magnesium alloy by HPT at room temperature for different numbers of turns with the microstructures before and after HPT investigated using scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Vickers microhardness (Hv) tests. Subsequently, tensile specimens are cut from the processed disks and pulled in tension to failure at temperatures of 473, 523, and 573 K and at strain rates in the range from 1.4 × 10 −4 to 1.4 × 10 −1 s −1 . The introduction of superplasticity in the HPT‐processed AZ80 is demonstrated for the first time with a maximum elongation of 645% at a testing temperature of 573 K. There is also evidence for low‐temperature superplasticity with an elongation of 423% at 473 K. The dominant mechanism for superplastic flow is grain boundary sliding with a strain rate sensitivity of m = 0.5 and an activation energy of Q = 73 kJ mol −1 . Abstract : Microstructure in the AZ80 disk sample processed by 10 turns of high‐pressure torsion (HPT) shows precipitates (Mg17 Al12 ) at grain boundaries and triple junctions (left image), and energy‐dispersive X‐ray spectroscopy (EDS) line scanning (right) demonstrates the changes in chemical composition of the matrix and precipitates. These nanoprecipitates effectively pin the grain boundaries, impede grain growth, and thereby improve the superplastic capability.